An evaluation of the inhibitions caused by legacy systems on digital transformation in a South African retail bank - Mantyi, Lukhanyiso (My University, 2020)
This research report investigates the inhibitions imposed by legacy systems on digital transformation strategies. The study focuses on the traditional retail bank, as these institutions contain traditional core systems that are complex to maintain and to replace. Moreover, the legacy can also be seen in business models that have previously been successful and are being disrupted by digital technology. The existing theory uncovers that transforming organisations ought to develop enabling capabilities to support digital transformation. It specifies that implementing new technology is not sufficient to successfully implement the strategies and gain a competitive advantage. The challenge that traditional banks are faced with is the navigation of archaic systems whilst driving innovation. Qualitative research in the form of semi-structured interviews with senior management was conducted. The population of the study comprises all employees of the Retail division of Bank X, South Africa. The sample was selected based on seniority as well as exposure to digital strategy formulation and implementation in the bank. The study found that there are gaps in the understanding of digital transformation within the bank. This disconnect permeates the implementation of the strategy and creates silos in execution. It was also found that the digital transformation strategy needs to be supported by skilled personnel, an enabling culture, a sound operating model, and modernisation mechanisms to deal with the current system architecture. These capabilities are on varying levels of maturity in the bank and have a direct impact on the implementation of the digital transformation strategy. A number of challenges were highlighted in the study relative to the research questions. To address the emerging challenges, six recommendations were made, namely defining digital transformation in the context of the organisation, clarification on the leadership of digital agenda, upskilling of the employees with digital skills, development of an architectural strategy that supports the digital strategy and investing in decision support tools to derive value from the data assets.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Digital transformation strategy; Digitisation; digital strategy; legacy systems; Core systems; banking industry; SDG-8: Decent work and economic growth